Analysis of the dynamics of sales volumes of the domestic machinebuilding complex - Martyniuk, Volodymyr; Tur, Nazarii (Видавництво Львівської політехніки, 2017)
The development of the machine-building industry for the last 5 years has been analyzed. The research of scientific sources on this issue was conducted. Trends in promising changes are revealed. The problems of functioning of machine-building enterprises are detailed and methods of their solution are proposed.
Keywords: competition; competitiveness; demand; investment attractiveness; engineering; innovative activity; modernization